Efektivitas Model Project Based Learning Berbantuan Media Trudare Terhadap Hasil Belajar Pendidikan Pancasila Siswa SDN 1 Sowan Lor - Hamidaturrohmah; Salmah (Penerbit STKIP PGRI Bangkalan, 2025)
Pancasila education is very important in building the character and identity of the Indonesian nation; The lack of understanding of these values can reduce social awareness among the younger generation, resulting in decreased participation in the application of national values in the future. This study aims to analyze the extent to which the Project Based Learning (PjBL) model supported by Truth or Dare (TRUDARE) media affects the learning outcomes of Pancasila Education of fifth grade students at SDN 1 Sowan Lor. The quantitative research method uses a non-equivalent pretest-posttest design with an unequal control group. The research sample consists of two groups, namely the experimental group using PjBL with TRUDARE media and the control group applying the conventional lecture method. The research tool is in the form of multiple-choice questions whose validity has been tested. The results of the normality test with a sig value of 0.200 and homogeneity with a sig value of 0.315 indicate that the data are normally distributed and homogeneous. The results of the paired t-test with a significance value of 0.000 indicate that there is a significant difference between the learning outcomes of the experimental class and the control class. The average post-test score in the experimental class increased significantly by -27.400 compared to the control class. This study demonstrates that the implementation of the PjBL model with TRUDARE media is effective in improving student learning outcomes by creating an active, enjoyable, and meaningful learning environment. Therefore, this model can be used as an alternative for teachers to improve learning outcomes, especially in Pancasila Education learning in elementary schools.